The Effect of Oil Price on Stock Market Returns with Moderating Effect of Foreign Direct Investment & Foreign Portfolio Investment: Evidence from Pakistan Stock Market - Usman, Muhammad; Siddiqui, Danish Ahmed (Asian Journal of Economic Modelling, 2019)
This paper investigates the moderating impact of FDI & FPI in the association of macro-economic variables along with Oil prices & Index returns. Monthly data has been used from the period 2005 to 2018. Efficient unit root & breakpoint unit root tests results indicate that all variables are stationary at 1st difference. Co-integration test results signify the presence of long-run relationship in model. GARCH (1,1) model has been applied for analyzing the volatility in the data series. Furthermore, least square method is employed to check dependency & fitness level of model. In order to investigate the moderating impact, regression technique has been applied. Findings of LSM technique indicate that index returns aren’t significantly dependent on macro-economic variables on 1st difference of data series because variables predicting behavior has been changed with respect to stationarity of data. Exchange rate & interest rate have negative significant association with index returns. Oil prices & foreign direct investment have positive relationship with stock market return. FDI & FPI are unable to moderate significantly model dynamics. For estimating the panel regression model, 11 different sectors data is used and results show that exchange rate & oil prices have positive significant impact on sector wise price change but interest rate has significant negative association.